Metamorfozy sovremennoj medijnoj aksiosfery (na materiale ukrainskih SMI) - Kuznecova, Tagʹâna V. (Stylistyka, 2020)
The article is devoted to axiological research on the informational space of modem Ukraine. The paper presents the axiological conception of mass-media communication, which has allowed us to determine the peculiarity of the media axiosphere and its socio-cultural determinants.